Bright Lights Become a Handbook: Theories, Ideas, History of Photography (KULT_online, 2012)
In 1979 the technical college of Bielefeld initiated a small conference which is nowadays an established event. The Bielefelder Fotosymposien are situated between theory and practice and are used as gathering places for all those who are interested in photography. The anthology Denkprozesse der Fotografie (Thought-Processes of Photography), edited by two professors and artists at Bielefeld, Martin Roman Deppner and Gottfried Jäger (in both cases brilliant practitioners), proposes to sum up 30 years of symposia of photography in Bielefeld.This aim ends up being more than fulfilled on both levels: graphically and in its content. Every symposium fills its own chapter, and is presented with a brief contextualization and a list of all presentations. This helps not only to clarify the circumstances but to dignify every participant.